Equivalent stress analysis of processing tube tension reducing of the new steel 33Mn2V for oil well tubes - Wang, Fuzhong (Strojniški vestnik, 2008)
Finite element method (FEM) is used for simulation of two-pass processing tube tension-reducing of the new steel 33Mn2V for oil well tubes. The simulated results visualise dynamic evolution of equivalent stress, especially inside the work-piece. It is shown that the non-uniform distribution of equivalent stress on the longitudinal and transverse sections is a distinct characteristic of the processing tube tension-reducing, which can be used as basic data for improving tool and technics design, predicting and controlling the micro-structural evolution for manufacturing oil well tubes.
Keywords: cevi; napetosti; jeklo; metoda končnih elementov; finite element method